An account of inter-lexical polysemy in Italian prepositions: The case of per, tra, attraverso - Francesco-Alessio Ursini; Yue (Sara) Zhang (Moderna Språk)
The goal of this paper is to offer an account of an inter-lexical polysemy pattern connecting the three Italian prepositions per, tra and attraverso. It is shown via a corpus study that these prepositions can cover several related senses (i.e. they are polysemous), and that some of their senses overlap (i.e. inter-lexical polysemy is attested), thereby forming a clear-cut (lexical) contrast set. It is suggested that current theoretical proposals of polysemy cannot directly account for these data, and thus a new model must be introduced. The paper introduces such a model by combining generative (cartographic) syntactic insights with a Semantic Maps analysis. It is thus suggested that inter-lexical polysemy patterns arise because prepositions share syntactically equivalent structures, but partially different sense values are assigned to these structures. Therefore, these prepositions partition the semantic sub-space of ‘section’ spatial relations in only partially overlapping manners. Consequences for theories of polysemy and their connections to syntactic accounts of prepositions are discussed.